BETWEEN SECULAR AND RELIGIOUS - DIGNITY AS THE HIGHEST VALUE OF THE HUMAN SPIRIT - Anna Laputko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
It is analyzed that the secular assertion of human dignity, rights and freedoms in its practical plane in certain periods of human history has been and is a great challenge for Christian churches. It is studied that the Christian understanding of human dignity, balancing on the border of its theoretical proclamation and its practical implementation, served to promote the ideas of humanism, its ability to resist destructive, degrading manifestations of social life forms, in the dialectic of social and religious forms of life. It is shown that the dignity of the individual is inseparable from the understanding of his rights and freedoms, and therefore, the struggle for dignity and human rights is an integral part of the preaching of the truths of Christianity.